Analisis Komparasi Pembiayaan Mudharabah dan Murabahah Terhadap Perkembangan UMKM di BMT Cabang Besuk Agung - Hidayati, Nurul; Roifah, Tri Nadhirotur; Kartikawati, Yeni (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This research intends to analyze and compare the influence of Mudharabah and Murabahah funding to the growth of Micro, Small, and Medium Enterprises (MSMEs) at Baitul Maal wat Tamwil (BMT) Besuk Agung branch, through a quantitative approach with comparative analysis. Data were obtained through questionnaires, interviews, and financing documentation from MSME actors who are customers of BMT Besuk Agung branch. The findings suggest that both types of financing contribute positively to the development of MSMEs, but Murabahah financing is proven to be superior to Mudharabah financing. Murabahah financing provides cost certainty, ease of margin calculation, and reduces the risk of loss for BMT Besuk Agung branch, so that it is more in demand by MSMEs. Meanwhile, mudharabah financing, although it offers a profit-sharing system, tends to be less than optimal in encouraging the development of MSMEs due to the high risk and uncertainty of business results. Based on these findings, BMT Besuk Agung branch is advised to continue developing the murabahah financing scheme to support the growth of MSMEs more effectively.